(untitled) (The Proceedings of The International Conference on Climate Change, 2021)
This research aims to study a change of rainfall and indicate levels of agricultural drought in the Southwest monsoon period of the northern region of Thailand by using the GMI. The rainfall data from June to September of the year 1987 to 2019 were collected from 21 meteorological stations over the northern region of Thailand. The data were used to create the maps of agricultural drought levels and to analyze the distribution of agricultural drought on the study period. Then, the distribution of total rainfall maps of each month and the trend of rainfall over the past 33 years were examined. The results showed that agricultural drought in Northern Thailand had no exact pattern. However, there was a drought impact on crops level in the lower part of Northern Thailand at the end of the Southwest monsoon period in 2019 with the GMI percentile score average (GMIpctsw) of 22.82 %. Furthermore, the severe drought impact and possible crop failure level were observed in the upper part of Northern Thailand in the same period. Moreover, the total rainfall sharply increased from June to August then decreased in September. The trend of total rainfall of the Southwest monsoon period (June to September) fluctuates along the study period with average value of 796.67 millimeter.